Sediment aluminum:phosphorus binding ratios and internal phosphorus loading characteristics 12 years after aluminum sulfate application to Lake McCarrons, Minnesota. (2nd January 2020) - James, William F.; Bischoff, Joseph M.
Abstract: James WF, Bischoff JM. 2019. Aluminum:phosphorus binding ratios and internal phosphorus loading characteristics 12 years after aluminum sulfate application to Lake McCarrons, Minnesota. Lake Reserv Manage. 36:1–13. Lake McCarrons, Minnesota, an urban eutrophic system (mean depth = 7.6 m, maximum depth = 17.4 m) located in the St. Paul metropolitan area, was treated in 2004 with ∼77 g Al/m 2 uniformly over depths >1.5 m to reduce internal phosphorus (P) loading. Sediment cores were collected at various depths and areas in the lake in 2016, 12 yr after the Al treatment, to examine concentrations and vertical distribution of Al, Al-bound P, the aluminum:Al-bound P (Al:P) binding ratio, and current anaerobic diffusive P flux. The Al floc became redistributed after application and varied with respect to the northwest–southeast (NW-SE) maximum fetch. Added Al was maximal in the SE area, exceeding nearly 180% of the target Al dose, and buried with up to 5 cm of sediment. In the NW, added Al was lower (14% to 34% of target Al dose) to not detected and dispersed in the upper 3 cm with little burial. Al-bound P increased with increasing added Al concentration over all stations. The molar Al:P binding ratio approached 10:1 in conjunction with lowest added Al concentrations found in the NW, suggesting P saturation and inefficient control of newly deposited redox P and corresponding diffusive P flux. Although SE areas had the greatest added Al, the molar Al:P binding ratio was > 30:1, suggesting poor binding efficiency and crystallization. This Al floc has become buried, and redox P in surface sediment now represents an important internal P load to the lake to be managed in the future.